Aseneth and the honeycomb apicultural keys to Joseph and Aseneth - Poirier, John C. 1963- (Leuven Paris Bristol, CT Peeters, 2024)
'[This book] makes three major contributions to Joseph and Aseneth studies: (1) it examines the details of Aseneth's encounter with the divine honeycomb and bees in the light of ancient apicultural beliefs and practices, (2) it uses the varying apicultural expertise displayed in the four main textual families to settle the heretofore intractable debate over which family preserves the earliest form of the work, and (3) it proposes a literary solution to a central concern of any attentive reader: the question of why Aseneth's heavenly visitor calls her a "city of refuge".' --
Includes indexes
Includes bibliographical references and sources (pages 173-197)
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Joseph and Aseneth; Bee culture -- Religious aspects; Bee culture -- Middle East -- History; Honey in literature; Apiculture - Aspect religieux